Economic Security and Democratic Capital: Why Do Some Democracies Survive and Others Fail? - Noguera-Santaella, J (Elsevier Inc., 2014)
We develop a theoretical framework where the chance of any given democratic society maintaining its democratic status is determined by two key factors: economic security and democratic capital. Our model predicts democracy breakdown is more likely (1) the lower the level of democratic capital, (2) the lower the anticipated growth in democracy, (3) the greater the anticipated growth after democracy breakdown, and finally, (4) the smaller the difference between anticipated growth in continued democracy and after democracy breakdown. We test the model using a newly constructed data set and the Polity IV data. We find that if expected economic growth under democracy is greater than anticipated economic growth under the alternative regime then the probability of breakdown is lower. Moreover, an increase in democratic capital decreases the probability of democracy breakdown. The country s most recent own democratic experience appears to have a more important impact on democracy survival, while the effect of foreign democratic capital cannot be distinguished from the time-specific shocks that are common to all countries in the world. © 2014 Elsevier Inc.